Is a Lead Isotope Ratios in Wine Good Marker for Origin Assessment? - Đurđić, Slađana; Stanković, Vesna; Ražić, Slavica; Mutić, Jelena (Frontiers in Chemistry, 2021)
Lead isotope ratio pattern (206Pb/207Pb, 208Pb/206Pb, 206Pb/204Pb, 207Pb/204Pb and 208Pb/204Pb) was analyzed in 59 samples of Serbian wine, from four geographical regions. By utilization of powerful inductively coupled plasma mass spectrometry (ICP-QMS), lead isotope ratios (LIRs) were used as unique "fingerprint", when combined with multivariate methods of analysis (Principal Component Analysis), provided information on the geographical origin of wine. In validation of ICP- QMS method and quantitative analysis, the certified reference material NIST SRM 981 was employed to test the mass-bias correction and thallium isotopes 203Tl and 205Tl (NIST SRM 997) as an internal standard. The obtained results were discussed in correlation with the corresponding values of LIRs of different European and Australian wines. In addition, the impact of anthropogenic Pb from different sources on the total Pb isotopic composition in Serbian wines was analyzed too. On the other side, the obtained values of Pb content were compared with the applicable health safety standards, according to the International Code of Oenological Practices.